La interpretación de Allison sobre la noción kantiana de ‘validez objetiva’ (2016)
Firstly, this article exposes the problem of the two parts to Kant’s “Deduction”; then it demonstrates how Allison interprets it and, in doing so, gives his author’s own interpretation of “Objective Validity” of the two categories. After that, the author analyses the contrast between that which Kant says about the difference between judgement of perception and the judgement of experience in the “Prolegomena” on the one hand, and on the other, the difference between the subjective and objective units of conscience as established in §§18-19 in “Deduction”. With Allison’s interpretation as a starting point, this contrast will allow to conclude whether the position taken by Kant in “Prolegomena” and Critique Of Pure Reason are consistent. If they are not, it is impossible to explain the fact the there are certain judgements without the participation of the pure concepts of understanding; On the other hand, if what Kant says in “Deductions” is considered a modification of what is written in “Prolegomena”, valid judgements would exist subjectively and objectively at the same time.